Management as a system transformer - A. I. Kovalev; T. V. Ivashkevich; O. N. Levchegov (Вестник СибАДИ)
The authors have proposed a graphic composition of a management system as a system-transformer. Creation of the system is the first step of predictive analytics and rational choice of research methods. The system is based on the resource and potential concept of management in various fields of activity. Basic composition, which reflects dynamic and static aspects of management can be transformed, according to industry sector, macro-and microeconomic factors of a moment, specific objectives of study.